1993
DOI: 10.1111/j.1600-0447.1993.tb03365.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders in young adults with chronic physical diseases since childhood as identified by the Present State Examination and the CATEGO program

Abstract: To find out whether long-term physical disorders in childhood increase the risk for mental disorder, we interviewed 407 young adults and compared their findings to a control group of 123 age-matched controls. The overall prevalence of mental disorders according to ICD-8 classification exceeded 20% in both groups. Depression and phobic disorders were the most common diagnostic syndromes, being most prevalent in women with motor handicaps or short stature. Only 7 patients had received psychotherapy, 5 for psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Recently, it has been suggested that rates of phobic disorders, with a 20% 6-month prevalence in one study (6), and eating disorders (7) may be elevated in diabetic patients as well. Indeed, in population-based and clinically ascertained samples, individuals with diabetes have higher rates of psychiatric disorders, particularly depression and possibly anxiety, than do medically well peers (6,8,(9)(10)(11)(12)(13). However, most of the relevant information concerns adults.…”
mentioning
confidence: 95%
“…Recently, it has been suggested that rates of phobic disorders, with a 20% 6-month prevalence in one study (6), and eating disorders (7) may be elevated in diabetic patients as well. Indeed, in population-based and clinically ascertained samples, individuals with diabetes have higher rates of psychiatric disorders, particularly depression and possibly anxiety, than do medically well peers (6,8,(9)(10)(11)(12)(13). However, most of the relevant information concerns adults.…”
mentioning
confidence: 95%
“…Depression is more treatment resistant when it coexists with other medical or psychiatric illness compared to patients without other underline disorder and which result in increasing mortality in chronic kidney disease patients [2]. Depression is well established as a prevalent mental health problem for people with CKD and is associated with increased morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies pertaining to chronic or acute illness in childhood were found (Pless et al 1989 ; Kokkonen & Kokkonen, 1993 ; Cohen et al 1998 ; Packham et al , 2002 ; Gaughan et al 2004 ; Goodwin, 2011 ; Ferro & Boyle, 2015 ; Khandaker et al 2014 ). Of these, five used a broad definition of infection/illness, and as such had heterogeneous diagnostic groups, while the other two referred to a specific infection/illness.…”
Section: Resultsmentioning
confidence: 99%
“…In a second study, the prevalence rates of mental disorders in adults who suffered from a variety of chronic physical illnesses in childhood were compared to age-matched controls (Kokkonen & Kokkonen, 1993 ). Similar to findings from Pless and colleagues, this study found no significant difference in the prevalence rates of all types of depression in young adults with childhood illness compared to healthy controls (13% v. 12%).…”
Section: Resultsmentioning
confidence: 99%